2018
DOI: 10.3748/wjg.v24.i13.1419
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection in subjects negative for high titer serum antibody

Abstract: AIMTo investigate the clinicopathological features of the patients testing negative for high titer serum anti-Helicobacter pylori (H. pylori) antibody.METHODSThe antibody titers were measured using antigens derived from Japanese individuals. 13C-urea breath test-positive individuals were defined as having H. pylori infection. We investigated the demographic characteristics, laboratory data, endoscopic findings including Kyoto classification of gastritis, and histology in negative-high titer patients without H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 38 publications
2
59
0
2
Order By: Relevance
“…When the serum anti-H. pylori antibody titer was ≥ 3.0 U/mL, the urea breath test or histology was added. If either the urea breath test or histology was positive, patients were considered positive for H. pylori [18,19]. An antibody titer < 3.0 U/mL or negative urea breath test was considered to indicate H. pylori negativity.…”
Section: Diagnosis Of H Pylori Infectionmentioning
confidence: 99%
“…When the serum anti-H. pylori antibody titer was ≥ 3.0 U/mL, the urea breath test or histology was added. If either the urea breath test or histology was positive, patients were considered positive for H. pylori [18,19]. An antibody titer < 3.0 U/mL or negative urea breath test was considered to indicate H. pylori negativity.…”
Section: Diagnosis Of H Pylori Infectionmentioning
confidence: 99%
“…The Kyoto classification score comprises parameters such as atrophy, intestinal metaplasia, enlarged folds, nodularity, and diffuse redness. The Kyoto classification score was reportedly associated with the risk of H. pylori infection and gastric cancer 15,[22][23][24][25] ; however, the change in Kyoto score before and Clinic on 6 September 2019 (approval no. S1909-U06).…”
Section: Introductionmentioning
confidence: 99%
“…The serum antibody titer was measured by an enzyme-linked immunoassay kit using antigens derived from Japanese individuals: E-plate Eiken H. pylori antibody II kit (Eiken Chemical, Tokyo, Japan). We defined a cut-off value of 10 U/mL was identified for H. pylori positivity as the manufacturer recommended[ 13 - 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Kyoto classification score consisted of scores in gastric atrophy, intestinal metaplasia, enlarged folds, nodularity, and diffuse redness[ 12 ]. Several studies have revealed the association of the Kyoto score with H. pylori infection[ 13 - 17 ] and gastric cancer risk[ 18 - 20 ]; however, the consistency of the Kyoto score with pathological findings has not been clarified. Therefore, this study aimed to investigate the relationship between the Kyoto score and pathological findings.…”
Section: Introductionmentioning
confidence: 99%